Evaluation of Drainage System Performance in Flood Control Efforts in Benua Melayu Darat Subdistrict, Pontianak City - Kurniawan, Pramudya; Ryanti, Eva; Syahrani, Deny; Muhtadi, Ahmad; Rabihati, Etty; Hafiyyan, Qalbi (International Journal of Research in Vocational Studies (IJRVOCAS), 2026)
Benua Melayu Darat, located in South Pontianak Regency, relies heavily on artificial drainage systems to control surface runoff and flooding. However, the area still frequently experiences flooding during high rainfall intensity. Therefore, this study was conducted to evaluate the performance of the drainage system in Benua Melayu Darat District from a hydraulic and non-technical perspective and to identify the dominant factors contributing to channel dysfunction. The evaluation began with hydrological and domestic wastewater analyses to determine the total water volume to be accommodated by the existing channels. A hydraulic analysis was then conducted to determine the channel’s design discharge. Direct field measurements were performed to assess channel dimensions and flow velocity, and non-technical analyses were conducted of sedimentation, waste, and land cover. The results showed that 45% of channels in Benua Melayu Darat District had inadequate capacity to accommodate rainfall and domestic wastewater. Non-technical factors, such as uncontrolled sedimentation rates and garbage blockages, also significantly disrupted channel function. This study shows the need to normalise dimensions and channels, implement low-impact development systems, such as retention ponds, strengthen maintenance programs to ensure adequate drainage, and provide public education on how to maintain or protect the environment to prevent flooding.